Quantitative imaging of lymph function - Sharma, Ruchi (2007)
Abstract Functional lymphatic imaging was demonstrated in the abdomen and anterior hindlimb of anesthetized, intact Yorkshire swine by using near-infrared (NIR) fluorescence imaging following intradermal administration of 100–200 μl of 32 μM indocyanine green (ICG) and 64 μM hyaluronan NIR imaging conjugate to target the lymph vacular endothelial receptor (LYVE)-1 on the lymph endothelium. NIR fluorescence imaging employed illumination of 780 nm excitation light (∼2 mW/cm2) and collection of 830 nm fluorescence generated from the imaging agents. Our results show the ability to image the immediate trafficking of ICG from the plexus, through the vessels and lymphangions, and to the superficial mammary, subiliac, and middle iliac lymph nodes, which were located as deep as 3 cm beneath the tissue surface. “Packets” of ICG-transited lymph vessels of 2–16 cm length propelled at frequencies of 0.5–3.3 pulses/min and velocities of 0.23–0.75 cm/s. Lymph propulsion was independent of respiration rate. In the case of the hyaluronan imaging agent, lymph propulsion was absent as the dye progressed immediately through the plexus and stained the lymph vessels and nodes. Lymph imaging required 5.0 and 11.9 μg of ICG and hyaluronan conjugate, respectively. Our results suggest that microgram quantities of NIR optical imaging agents and their conjugates have a potential to image lymph function in patients suffering from lymph-related disorders. the impairment of lymphatic transport capacity occurs due to either 1) lymph vessel damage and subsequent insufficient repair processes, or 2) congenital defects leading to abnormal lymph vessel development. Regardless of the cause, the impairment causes fluid and protein accumulation, which in turn leads to lymphedema. Lymphedema is a lifelong condition progressing from swelling and scarring to immune dysregulation and malnutrition. No curative treatment exists for lymphedema that afflicts 300 million people worldwide (44). Congenital or primary lymphedema afflicts 1 in every 6,000 newborns (go to http://grants.nih.gov/grants/guide/pa-files/PA-04-071.html for more information) and can also appear at the onset of puberty (10). Acquired or secondary lymphedema is caused by the filaria parasite (in a condition referred to as elephantiasis) or by trauma due to radiation therapy, infiltrating cancer, surgery, or infection. In developing-world countries, 100 million people are afflicted worldwide by filariasis. In Western countries, acquired lymphedema afflicts three to five million people (32a). The etiology for trauma-associated, acquired lymphedema is thought to arise from the interruption of lymph channels coupled with postsurgical infection or radiation-induced skin reaction. The onset of symptoms, however, can occur from days, weeks, to years following the initial trauma, striking at a rate cited between 6 and 62.5% of breast cancer survivors who have undergone axillary lymph node dissection (1, 26, 38), up to 64% of all patients who undergo groin dissections (8), and 25% of all radical hysterectomy patients (4). Little is known about the molecular or functional basis of acquired lymphedema or which persons could be at risk for the condition. There is a paucity of strategies for predicting or managing lymphedema due in part to the lack of diagnostic imaging approaches to noninvasively and routinely measure lymphatic function. Since lymph function is also implicated in diseases of significant prevalence [such as diabetes (16), obesity (13), cancer (28), and asthma (2)], the ability to quantitatively image lymph function could have substantial impact on the health of the world's population. In this contribution, we present near-infrared (NIR) fluorescence lymph imaging as a new method to sensitively image lymph vasculature and quantitatively assess lymph function non-invasively within intact subjects. The feasibility of NIR fluorescence lymph imaging is demonstrated in a swine model that mimics the human dermis and lymph plexus architecture. We show that through the intradermal delivery of 100–200 μl of a nonspecific NIR fluorescent dye, we can visualize lymph propulsion across lymph vessels as well as compute the velocity of lymph flow and the frequency of lymph propulsion. In addition, we demonstrate a lymph molecular imaging agent based on hyaluronan, a ligand for lymph vascular endothelial receptor (LYVE-1) (3, 23) to molecularly target the lymphatic vasculature. In materials and methods, we describe the fluorescent contrast agents employed, animal models, optical imaging instrumentation, and image analysis to quantify lymph function. Dynamic lymph imaging results from the intradermal administration of indocyanine green (ICG), and the hyaluronan conjugate imaging agents are presented with movies presented in the on-line supplemental section. To place our work in context of other lymph imaging modalities, we briefly discuss the state-of-art in clinical and developmental lymph imaging approaches. Finally, we conclude by commenting on the clinical translation of NIR fluorescence enhanced optical imaging for quantifying lymph function in lymphatic diseases